DAYA TARIK WISATA BUDAYA DI DESA WISATA PULAU BELIMBING KECAMATAN KUOK KABUPATEN KAMPAR PROVINSI RIAU - Nur Azizah; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to determine the cultural attractions in the tourist village of leatherback island Kuok District of Kampar regency of Riau province and identifies cultural tourist attraction in the tourist village of leatherback island Kuok District of Kampar regency in Riau province.This study used descriptive qualitative method to analyze the problem. The sampling technique used was purposive sample. While data collection techniques in this study using observation, interviews, and documentation and data analysis techniques using data reduction, data display and conclusion drawing.The results of this study is there are 2 sub variables into a cultural tourist attraction in the tourist village of the island leatherback District of Kuok Kampar regency Riau province that cultural relics have an indicator objects, heritage buildings, museums and the living culture who have an indicator ceremony / ritual, customs, art shows and events.